Rehabilitation using hybrid technique for feeding plate fabrication in a 3-month-old infant with cleft palate defect utilising digital and conventional method: A case report - Manu Rathee; Sujata Chahal; Prachi Jain; Maqbul Alam; S Divakar; Sandeep Singh (Wolters Kluwer Medknow Publications, 2024)
Cleft palate leads to difficulty in suckling, speech abnormalities, dental problems, hearing loss and middle ear infections. Feeding plate acts as a barrier between the oral and nasal cavities allowing the normal development of jaws and enhanced nutritional supply to the patient. Fabrication of the feeding plate using digital means provide better adaptability due to the engagement of all the possible favourable anatomic undercuts, thereby, providing better retention. This case report discusses the hybrid technique including both the digital and conventional means for fabrication of a feeding plate to obturate the defect between the oral and nasal cavity.